Bionic vision: system architectures – a review. (January 2012) - Guenther, Thomas; Lovell, Nigel H; Suaning, Gregg J
The concept of an electronic visual prosthesis has been investigated since the early 20th century. While the first generation of long-term implantable devices were defined by the turn of the millennium, the greatest progress has been achieved in the past decade. This review describes the current state of the art of visual prosthesis investigated by more than two dozen active groups in this field of research. The focus is on technological solutions in regard to long-term safety of materials, electrode–tissue interfaces and encapsulation technologies. Furthermore, we critically assess the maximum number of stimulating electrodes each technological approach is likely to provide.